Impact of anthropogenic factor on changes in physical and chemical properties of chernozems in the lake Sevan basin of the republic of Armenia - Kroyan Samvel; Tovmasyan Suren; Margaryan Anush (BIO Web of Conferences, 2024)
This article focuses on the study of changes in the physical and chemical composition of mountain chernozems of the Republic of Armenia under the influence of an anthropogenic factor. It is established that under long-term and unsystematic agricultural use of chernozems in arable variants of soils, in comparison with virgin soil, significant changes in their physical and chemical properties are observed. Especially, absorption capacity decreases as a result of reduction of such important bases as absorbed calcium and magnesium. To improve the physical and chemical properties, increase fertility, effective use, and protection of mountain chernozems of the Lake Sevan basin of the Republic of Armenia, it is necessary to develop and apply a complete scientifically substantiated system of agrotechnical measures.